Systems Approach to Engineering Problems: Some Aspects of Application to Transport - Planning Commission (Planning Commission Government of India, 1982)
The document “Systems Approach to Engineering Problems: Some Aspects of Application to Transport” examines the application of systems analysis and operations research to urban and regional transport planning in India. Traditional reliance on historical data has become inadequate, necessitating analytical techniques that integrate engineering, economics, and geography to model complex transport systems. The report discusses the development of transport models, including macroeconomic input-output frameworks, the “share and shift” method, and the gravity model, which forecast traffic demand and modal splits for rail and road. Findings indicate substantial growth in traffic activity, with increased tonne-kilometers and evolving reliance on rail transport influenced by cost dynamics. While acknowledging critiques of the systems approach, the paper emphasizes its utility in informed policy-making, efficient resource allocation, and scenario analysis. The study advocates sustained interdisciplinary application and advanced computer modeling to optimize transport policy outcomes and support long-term planning.
Planning Commission Government of India (UNDP Transport Policy Planning Project) January 1982
Planning Commission Government of India (UNDP Transport Policy Planning Project) January 1982
Keywords: Systems Approach; Transport Planning; Urban Planning; Operations Research; Traffic Forecasting; Transport Modeling; Macroeconomic Models; Gravity Model; Modal Split; Interdisciplinary Approach; Policy Analysis; Regional Transport